Quality, bioactive compounds, and antioxidant activity of serrano chili peppers cultivated in volcanic rock-vermicompost and nutrient solutions - Cruz-Crespo,Elia (Pontificia Universidad Católica de Chile. Facultad de Agronomía e Ingeniería Forestal, 2015)
E. Cruz-Crespo, M.T. Sumaya-Martínez, Á. Can-Chulim, J. Pineda-Pineda, R. Bugarín-Montoya and G. Aguilar-Benítez. 2015. Quality, bioactive compounds, and antioxidant activity of serrano chili peppers cultivated in volcanic rock-vermicompost and nutrient solutions. Cien. Inv. Agr. 42(3): 375-384. The concentration of antioxidant compounds, the antioxidant activity, physical quality characteristics, and the yield of serrano chilies (Capsicum annuum L.) are affected by agricultural practices, such as the use of vermicompost in containers combined with chemical fertilizers, the investigations of which have focused on yield. A study was performed to determine whether vermicompost mixed with volcanic rock and the ionic composition of the nutrient solution affect the variables mentioned above. Serrano chilies were planted in volcanic rock:vermicompost in the following proportions 100:0, 80:20 and 60:40 and were watered with Steiner nutrient solution at 25, 50, and 75%. Interaction of the factors was determined for the fresh weight of the fruits. Fruit length, diameter, number, weight, yield, firmness, hue, and chroma increased with the nutrient solutions at 50 and 75%. Ascorbic acid levels fell with the solutions at 50 and 75%, and total phenols and antioxidant activity increased with the solutions at 25 and 50%. The 80:20 and 60:40 volcanic rock:vermicompost substrates similarly increased the length, diameter, number, weight, total phenols and antioxidant activity of the fruit. Yield increased with a greater proportion of the vermicompost. The solution at 50% and the volcanic rock:vermicompost mixture 80:20 were the best conditions for the content of phenolic compounds, antioxidant activity, as well as diverse quality variables, although the 60:40 proportion was more favorable for yield.